Genome-Wide SNP Data Revealed the Extent of Linkage Disequilibrium, Persistence of Phase and Effective Population Size in Purebred and Crossbred Buffalo Populations - Deng, Tingxian; Liang, Aixin; Liu, Jiajia; Hua, Guohua; Ye, Tingzhu; Liu, Shenhe; Campanile, Giuseppe; Plastow, Graham; Zhang, Chunyan; Wang, Zhiquan; Salzano, Angela; Gasparrini, Bianca; et al. (Frontiers in Genetics, 2019)
Linkage disequilibrium (LD) is a useful parameter for guiding the accuracy and power of both genome-wide association studies (GWAS) and genomic selection (GS) among different livestock species. The present study evaluated the extent of LD, persistence of phase and effective population size (Ne) for the purebred (Mediterranean buffalo; n=411) and crossbred [Mediterranean × Jianghan × Nili-Ravi buffalo, n=9; Murrah × Nili-Ravi × local (Xilin or Fuzhong) buffalo, n=36] buffalo populations using the 90K Buffalo SNP genotyping array. The results showed that the average square of correlation coefficient (r2) between adjacent SNP was 0.13 ± 0.19 across all autosomes for purebred and 0.09 ± 0.13 for crossbred, and the most rapid decline in LD was observed over the first 200 kb. Estimated r2 ≥ 0.2 extended up to approximately 50 kb in crossbred and 170 kb in purebred populations, while average r2 values ≥ 0.3 were respectively observed in the approximately10 kb and 60 kb in the crossbred and purebred populations. The largest phase correlation (RP,C = 0.47) was observed at the distance of 100 kb, suggesting that this phase was not actively preserved between the two populations. Estimated Ne for the purebred and crossbred population at the current generation was 387 and 113 individuals, respectively. These findings may provide useful information to guide the GS and GWAS in buffaloes.